Understanding The Effect of WFH (Work from Home) On Individual Performance of ITB Dormitory Tutor (Journal of Business and Management, 2022)
Abstract. This pandemic has suddenly changed how people work and forcing everyone to adapt, the ITB Dormitory Tutor is no exception. ITB Dormitory Tutors are second-year to final year students who are responsible for fostering the character of first-year students. This organization is under Direktorat Kemahasiswaan Institut Teknologi Bandung (DITMAWA ITB) and Direktorat Sarana dan Prasarana ITB. The author found a decrease in performance of ITB Dormitory Tutors during WFH in the form of KPI achievement decreasing from 84.80% to 80.39%. The author adapts the MARS model using a quantitative approach to determine which factors causes a decrease on the individual performance of ITB Dormitory Tutors. MARS model of Individual Performance and Behavior consists of 4 variables, namely Motivation (M), Ability (A), Role Perception (RP) and Situational Factor (SF). The tool used was a questionnaire which is distributed through online to find out which indicators were approved by the ITB Dormitory Tutor. The author took 83 samples. The data were analyzed by Microsoft Excel for validity and reliability test. The results of this study indicate that the cause of the decrease in Individual Performance of ITB Dormitory Tutors during WFH is the Situational Factor (SF) and Mental Ability (A) variables.Keywords: WFH, MARS model, Individual Performance, ITB Dormitory Tutor, quantitative